PRODUCT SALES USING AN AFFILIATE SYSTEM AMONG STUDENTS IN BANDA ACEH VIA THE TIKTOK APP: A PERSPECTIVE FROM FIQH MUAMALAH - Muhammad Farhan Afdhal; Anggie Yolanda Ritonga (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
This study focuses on the affiliate system mechanism on TikTok, potential deviations from Sharia principles in its implementation, and an analysis of its compatibility with fiqh muamalah based on the concepts of ju’alah and wakalah bil ujrah contracts. The method used is qualitative research. Primary data was obtained through interviews with five students from various universities in Banda Aceh who are active as TikTok affiliates and observations of the promotional content they created. Meanwhile, secondary data was obtained through a literature review of Islamic jurisprudence, economics, and contract law. The study results indicate that the TikTok affiliate system is fundamentally acceptable under Islamic law, provided it meets the valid contract requirements, such as clarity of the subject matter, compensation, and mutual consent between the parties. However, it was found that most affiliates lack an understanding of the contract concept, there is ambiguity in commission distribution, and promotional practices often mislead consumers.